2014
DOI: 10.1186/1471-2164-15-961
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide cloning, identification, classification and functional analysis of cotton heat shock transcription factors in cotton (Gossypium hirsutum)

Abstract: BackgroundHeat shock transcriptional factors (Hsfs) play important roles in the processes of biotic and abiotic stresses as well as in plant development. Cotton (Gossypium hirsutum, 2n = 4x = (AD)2 = 52) is an important crop for natural fiber production. Due to continuous high temperature and intermittent drought, heat stress is becoming a handicap to improve cotton yield and lint quality. Recently, the related wild diploid species Gossypium raimondii genome (2n = 2x = (D5)2 = 26) has been fully sequenced. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 67 publications
6
47
0
Order By: Relevance
“…Hsfs were initially characterized and cloned in yeast ( Saccharomyces cerevisiae ) (Sorger and Pelham, ), followed by various plants (Huang et al ., ; Singh et al ., ; Yabuta, ). With the genome sequencing of more and more plant species, the Hsf gene family has been thoroughly identified and characterized in alfalfa (Friedberg et al ., ), Arabidopsis thaliana (Guo et al ., ), rice ( Oryza sativa L.) (Chauhan et al ., ; Jin et al ., ; Wang et al ., ), maize (Lin et al ., ), Populus trichocarpa and Medicago truncatula (Wang et al ., ), Glycine max (Chung et al ., ), wheat (Chauhan et al ., ), Chinese cabbage (Song et al ., ), pepper ( Capsicum annuum L.) (Guo et al ., ), legume (Lin et al ., ), cotton ( Gossypium hirsutum ) (Wang et al ., ), soybean (Li et al ., ), pear ( Pyrus bretschneideri ) (Qiao et al ., ), Brassica rapa pekinensis (Huang et al ., ), Populus euphratica (Shen et al ., 2015), tea plant ( Camellia sinensis ) (Liu et al ., ), strawberry ( Fragaria vesca ) (Hu Y et al ., ) and wild Chinese grapevine ( Vitis pseudoreticulata ) (Hu et al ., ). So far, plant Hsfs have been found to be widely involved in plant development, heat stress, drought stress, salt stress and the plant disease response (Almoguera et al ., ; Cheng et al ., ; Giesguth et al ., ; Hwang et al ., ; Tanabe et al ., ; Yabuta, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hsfs were initially characterized and cloned in yeast ( Saccharomyces cerevisiae ) (Sorger and Pelham, ), followed by various plants (Huang et al ., ; Singh et al ., ; Yabuta, ). With the genome sequencing of more and more plant species, the Hsf gene family has been thoroughly identified and characterized in alfalfa (Friedberg et al ., ), Arabidopsis thaliana (Guo et al ., ), rice ( Oryza sativa L.) (Chauhan et al ., ; Jin et al ., ; Wang et al ., ), maize (Lin et al ., ), Populus trichocarpa and Medicago truncatula (Wang et al ., ), Glycine max (Chung et al ., ), wheat (Chauhan et al ., ), Chinese cabbage (Song et al ., ), pepper ( Capsicum annuum L.) (Guo et al ., ), legume (Lin et al ., ), cotton ( Gossypium hirsutum ) (Wang et al ., ), soybean (Li et al ., ), pear ( Pyrus bretschneideri ) (Qiao et al ., ), Brassica rapa pekinensis (Huang et al ., ), Populus euphratica (Shen et al ., 2015), tea plant ( Camellia sinensis ) (Liu et al ., ), strawberry ( Fragaria vesca ) (Hu Y et al ., ) and wild Chinese grapevine ( Vitis pseudoreticulata ) (Hu et al ., ). So far, plant Hsfs have been found to be widely involved in plant development, heat stress, drought stress, salt stress and the plant disease response (Almoguera et al ., ; Cheng et al ., ; Giesguth et al ., ; Hwang et al ., ; Tanabe et al ., ; Yabuta, ).…”
Section: Introductionmentioning
confidence: 99%
“…Heat shock transcription factors (HSFs) are involved in the regulation of tolerance to biotic and abiotic stresses (reviewed by Wang et al, 2014b). In avian cells, it was shown that the inhibition of the 26S proteasome induced the expression of HSFs and, consequently, of the key heat shock proteins (HSPs) HSP70 and HSP90, even in the absence of heat stress (Kawazoe et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to high temperature in cotton plants showed that GhHsfs39 demonstrated the most rapid response to the heat shock. It has been suggested that a differential expression of Hsfs may thus play a role in the fiber development that requires further study [89].…”
Section: Characterization Of Specific Genes For Cotton Fibermentioning
confidence: 99%